2015
DOI: 10.1002/pa.1574
|View full text |Cite
|
Sign up to set email alerts
|

Internal audit public sector capability: a case study

Abstract: Internal auditing is an essential part of governance and can be a valuable asset to public sector institutions. However, for public sector internal auditing to effectively support management, the internal audit function (IAF) should be capable. The question arises as to how the capability of public sector IAFs can be measured. The Institute of Internal Auditors Research Foundation published the Internal Audit Capability Model (IA-CM) in 2009 to provide a capability self-assessment tool for public sector IAFs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 10 publications
0
13
0
2
Order By: Relevance
“…An increase in the quality of internal auditors by 1 unit will increase the fraud prevention variable by 0.343, assuming the other variables are constant. The result is in line with the research of Yusof et al ( 2019), Sari et al (2019), Putu et al (2017), Janse (2016. This result is not in line with the research of Mui (2018), Lyinomen & Nkechi (2016) The Government Internal Control System (SPIP) affects fraud prevention through the quality of internal auditors…”
Section: The Quality Of Internal Auditors Affects Fraud Preventionmentioning
confidence: 54%
“…An increase in the quality of internal auditors by 1 unit will increase the fraud prevention variable by 0.343, assuming the other variables are constant. The result is in line with the research of Yusof et al ( 2019), Sari et al (2019), Putu et al (2017), Janse (2016. This result is not in line with the research of Mui (2018), Lyinomen & Nkechi (2016) The Government Internal Control System (SPIP) affects fraud prevention through the quality of internal auditors…”
Section: The Quality Of Internal Auditors Affects Fraud Preventionmentioning
confidence: 54%
“…For instance, some authors adduce evidence of management support and effectiveness of the internal audit system. (Dellai et al, 2016;Pappe, 2014;Alzeban and Gwilliams, 2014;van Rensburg & Coetzee, 2016) among others. On the other hand, few studies found no relationship between management support and the effectiveness of internal audit systems.…”
Section: Overview Of Literaturementioning
confidence: 99%
“…Unam et al (2014), the extent to which internal controls practices affect the internal audit effectiveness is moderate. Arena and Sarens (2015), Rose et al (2013) and van Rensburg & Coetzee (2016) also discussed the concept of management support and effectiveness. The objective of the internal audit system is to help members of organizations to effectively discharge their responsibilities.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…This aspect was influenced by unethical issues that hamper the internal audit role on achieving procurement performance. These include but not limited to the failure to detect fraud, corruption and malpractices within the organization (Janse van Rensburg & Coetzee, 2016). Similarly, other literature point out that competent and qualified staff influence the effective role of internal auditing in the parastatal organizations (Mullins, 2015).…”
Section: Empirical Reviewmentioning
confidence: 99%